Analysis of green total factor productivity in OECD and BRICS countries: based on the Super-SBM model. Issue 9 (30th August 2022) - Sun, Xiangxiang
Abstract: To address the conflict between environmental constraints and fast economic growth, as well as to coordinate green growth strategies between developing and developed countries, improving green total factor productivity (GTFP) is an important way to accelerate the green and low-carbon transformation and get rid of the problems of environment and resources. Therefore, it is significant to analyze and compare the GTFP of Organization for Economic Cooperation and Development (OECD) and BRICS (i.e. Brazil, Russia, India, China and South Africa) countries. By applying the Super-SBM model, our study analyzes the distribution characteristics and the evolving trend of GTFP. The empirical results indicate that: (1) The GTFP of BRICS countries has significantly improved, but there is still a significant gap compared with OECD countries. (2) Brazil, Luxembourg and Norway's GTFP values are higher than others. (3) Among the BRICS countries, Brazil exhibits the highest value and China has the minimum value, which was far ahead in energy consumption and PM2.5. (4) In the analysis of OECD countries, Hungary displays the lowest average value and Luxembourg has the highest average value. As such, some policy implications improve green and low-carbon development. HIGHLIGHTS: This study uses the Super-SBM model considering undesirable outputs to estimate the green total factor productivity (GTFP). The GTFP of OECD countries is higher than that of BRICS countries as a whole. Hungary displays the lowest average value and Luxembourg has the highest average value. Brazil exhibits the highest value and China has the minimum value, which was far ahead in energy consumption and PM2.5.